Primary Polydipsia in a Toddler: A Rare Case - Yousef Ansara MD; Amanda Siniora MD; Laith Ayasa MD; Mustafa Nabilsi MD; Tareq Hindi MD (SAGE Publishing, 2024)
Primary polydipsia (PP) is a rare but significant clinical entity in pediatric patients. Here, we present the case of a 16-month-old female referred to our center due to recurrent episodes of electrolyte imbalances. Initially admitted for management of a viral illness, she experienced unexplained electrolyte disturbances, prompting subsequent admissions marked by similar disruptions. Despite stabilization and discharge, her condition persisted. Pre-referral laboratory findings revealed significant electrolyte abnormalities alongside polyuria symptoms. Investigations unveiled a history of frequent heavy wet diapers and increased thirst. Further tests including a water deprivation test excluded diabetes insipidus. Following the restriction of water intake and careful monitoring, her condition markedly improved. This case emphasizes the importance of thorough evaluation in persistent electrolyte imbalances in toddlers, highlighting the role of polyuria as a contributing factor and the efficacy of targeted interventions in managing such cases.